Break to regional centralism: ilo province advances with greater private investment and GDP, 2001-2019 - Flores Arocutipa, Javier Pedro (2020)
Objective: To demonstrate that the Ilo province, not being capital, centralizes private investment, employment and added value; more than in other 19 districts of Moquegua region in the period 2001 – 2019. Method: It is a basic, explanatory, non-experimental study, the economic censuses of 2001 and 2008 are analyzed data from the Central Reserve Bank of Peru, the National Institute of Statistics and Informatics and the statisticians R, R2, and ANOVA were applied, in the SPSS 25 and Eviews 10 Software. Results: Ilo in 1940 had 1656 inhabitants and 66,876 in 2018, in 78 years it has multiplied by 40. The number of banks is higher than in 18 districts. At the 2008 economic census, the province of Ilo concentrated the largest number of companies, jobs, assets and assets; after 2008, this concentration has increased in relative terms, not absolute though. In 2019, Ilo concentrates the 68.8% of the region's credits. Conclusions: There are differences in the investment levels expressed in placements, in the gross value of production between the districts of Ilo and Moquegua. Credit growth rates in Ilo are higher than in other districts.